The tumor suppressor inhibitor of growth 4 binds double‐stranded DNA through its disordered central region. Issue 2 (22nd December 2016) - Ormaza, Georgina; Medagli, Barbara; Ibáñez de Opakua, Alain; Rodríguez, Jhon A.; Merino, Nekane; Villate, Maider; Onesti, Silvia; Blanco, Francisco J.
Abstract : The tumor suppressor inhibitor of growth 4 (ING4) regulates chromatin structure by recruiting the histone acetyl transferase complex HBO1 to sites with histone H3 trimethylated at K4. ING4 dimerizes through its N‐terminal domain and recognizes H3K4me3 by the C‐terminal plant homeodomain (PHD). The central region of ING4 is disordered and contains the nuclear localization signal. Here, utilizing electrophoresis and nuclear magnetic resonance, we show that ING4 binds double‐stranded DNA through its central region with micromolar affinity. Our findings suggest that the cooperativity arising from the presence of two DNA‐binding regions in the ING4 dimer, as well as two H3K4me3‐binding PHD fingers, may strengthen nucleosome binding and HBO1 complex recruitment. Abstract :